2022
DOI: 10.3390/ani12111413
|View full text |Cite
|
Sign up to set email alerts
|

Cats and SARS-CoV-2: A Scoping Review

Abstract: Since the beginning of the COVID-19 pandemic, various animal species were found to be susceptible to SARS-CoV-2 infection. The close contact that exists between humans and cats warrants special attention to the role of this species. Therefore, a scoping review was performed to obtain a comprehensive overview of the existing literature, and to map key concepts, types of research, and possible gaps in the research. A systematic search of the databases PubMed, GoogleScholar, and Scopus and the preprint servers me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 90 publications
0
16
1
Order By: Relevance
“…In addition to the persistent inter-host transmission of the virus, chronic infection in immunocompromised (or in healthy) individuals is an important source of the emergence of new variants by which the virus could acquire mutations and evolve to gain increased infectivity and immune evasion ( 34 36 ). Moreover, SARS-CoV-2 is now capable of infecting a variety of animal species, including dogs, house cats and rodents ( 37 , 38 ), suggesting that these host animals can serve as a large reservoir from which new viral variants can be developed through recombination between different strains similarly as Delta-Omicron recombinant viruses were developed ( 39 ). Such variants may spill over to humans, followed by reverse spill over from humans to other animal species in a repeated manner, necessitating advanced preparedness for the future emergence of zoonotic sarbecoviruses, including the development of pan-sarbecovirus vaccines and broadly nAbs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the persistent inter-host transmission of the virus, chronic infection in immunocompromised (or in healthy) individuals is an important source of the emergence of new variants by which the virus could acquire mutations and evolve to gain increased infectivity and immune evasion ( 34 36 ). Moreover, SARS-CoV-2 is now capable of infecting a variety of animal species, including dogs, house cats and rodents ( 37 , 38 ), suggesting that these host animals can serve as a large reservoir from which new viral variants can be developed through recombination between different strains similarly as Delta-Omicron recombinant viruses were developed ( 39 ). Such variants may spill over to humans, followed by reverse spill over from humans to other animal species in a repeated manner, necessitating advanced preparedness for the future emergence of zoonotic sarbecoviruses, including the development of pan-sarbecovirus vaccines and broadly nAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Cases were reported among farm minks’ farmworkers ( 5 , 32 ) and there was a recent case of cat to human transmission in Thailand ( 4 ). Cats usually shed low amounts of virus ( 15 , 19 , 33 , 34 ) and given that since the beginning of the pandemic by December 2019, only a few transmission cases were reported until now, the companion animal-to-human transmission route may not the main source of virus circulation. However, apart from the precautions clinical veterinarians should take when dealing with sick animals, the most important potential role of either companion, production or wild animals in the pandemic might be to act as reservoirs of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Cats are more susceptible to SARS-CoV-2 than dogs ( 14 ). Several studies revealed that the virus replicates only in the upper respiratory tract of cats and this replication was not associated with severe disease or death, except in kittens or cats with comorbidities ( 15 , 16 ). Cats can transmit the infection to other cats ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cats are susceptible to SARS-CoV-2 infection and show in general no to only mild clinical signs, as reported in several field and experimental studies reviewed and summarized by [ 8 , 35 , 36 ]. However, there is limited information available about the immune response shortly after infection, which is necessary to strengthen our knowledge about the pathogenesis of SARS-CoV-2 in cats.…”
Section: Discussionmentioning
confidence: 99%